EFFECT OF LIGNOSELULOLITIC FUNGUS TO ENZIMATIC ACTIVITY, FIBER FRCTION, AND DIGESTIBILITY ON FERMENTATION PROCESS OF COCOA POD - Engkus Ainul Yakin; Zaenal Bachruddin; Ristianto Utomo; Ria Millati (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
The study was conducted to determine the enzyme activity, fiber fraction and digestibility in the fermentation process of cocoa pod. The substrate was used the cocoa pod while the fungi used Phanerochaete chrysosporium, Pleurotus ostreatus and Schizophyllum commune. Preparation of cocoa pod was chopped, finely ground and then dried. Preparation of fungi by growing fungi in liquid medium. Research methodology was the fermentation conducted with different fungi used four treatments and five replications. T1 = fermentation of cocoa pod without fungi addition, T2 = fermentation of cocoa pod with P. chrysosporium addition, T3 = fermentation of cocoa pod with P. ostreatus addition, and T4 = fermentation of cocoa pod with S. commune. Fermentation used Erlenmeyer 250 ml and weight of cocoa pod was 100 gram. Fungi added on 5% from substrat weight bassis dry matter. Variables observed was enzyme activity, fiber fraction and digestibility . This study was designed using research design completely randomized design with a unidirectional pattern analysis of variance. Significant variables followed Duncan’s multiple range test. The results showed fermentation used P. chrysosporium has highest lignin peroxidase enzyme activity of 0.52±0.04 U/mL and mangan peroxidase 0.06±0.00 U/mL, neutral detergent fiber 75,54±0,41%, acid detergent fiber 68,10±0,30%, lignin 26,86±0,19%, cellulose 27,17±0,25%, hemicellulose 6,77±0,52%, dry matter digestibility 69,70±0,43% and organic matter digestibility 69,59±1,03%. The conclusion from this research that the fermentation by using fungi P. chrysosporium addition has the best result to degradated lignin.